Editorial - Ratnalikar, N. V. (Journal of Engineering Education Transformations, 2010)
It was the 40 th ISTE Annual Convention being held at Sivkashi (60 km away from Madurai, T.N.). The Convention was held from 2 to 4 December 2010 and the Convention theme was "Foreign Universities in India-Challenges and Opportunities". On the 2nd day i.e. on 3 rd Dec 2010, a panel discussion was organized on the Convention theme and seven Vice Chancellors of Technological Universities were the panelists. The discussion went on very well, as an interactive session, should. At the end of the panel discussion, the Chairman, Dr. Murugesan, v.c. of Anna University of Technology, Madurai, expressed happiness and thanked the ISTE for bringing the v.c. s together on a common platform to discus a matter of common interest and also to interact with each other. Other v.c. s also followed him, in thanking the ISTE.